PERSPEKTIF TEORI KOGNITIF PADA KESULITAN BELAJAR DALAM KURIKULUM MERDEKA - Pratiwi, Adisty Zulfa; Salamah, Nayla Siti Kurnia; Chadidjah, Sitti (STAI Pelabuhan Ratu, 2024)
This article discusses the perspective of cognitive theory regarding learning difficulties in the context of the Merdeka Curriculum. The Merdeka Curriculum, implemented in Indonesia, aims to provide more freedom to students and teachers in the learning process. However, its implementation still faces various challenges, one of which is the learning difficulties experienced by students. This article examines how cognitive theory can be used to understand and address these learning difficulties. By adopting views from several major cognitive theories such as information processing theory, Piaget's cognitive development theory, and Bandura's social learning theory, this article explains the cognitive factors that influence students' learning abilities. In addition, this article also provides recommendations for learning strategies that align with cognitive principles to help students overcome their learning difficulties. Through this approach, it is expected to create a more inclusive and effective learning environment within the Merdeka Curriculum.